PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN WAROENG SPESIAL SAMBAL “SS” CABANG SAMPANGAN - Dwi Rita Pangestuti, 14.05.51.0118; Liana, Lie (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the effect of product quality, price and quality of service to customer satisfaction on Waroeng Special Sambal branch Sampangan. Analyzer used multiple regression, as for to test hypothesis using t test. Data collection through questionnaires with measurements using Likert scale 5 (five) alternative answers. The object of research on Waroeng Special Sambal "SS" branch Sampangan, with the number of samples 100 respondents by using sampling technique non probability sampling with purposive sampling collection method. The results showed that: The quality of the product has a positive and significant impact on customer satisfaction Price affects negatif and not significant to customer satisfaction Service quality has a positive and significant effect on customer satisfactio Keywords : Product Quality, Price, Service Quality, Customer Satisfaction